AD, Volume 34, n° 2, 2009 - Full Issue - journal system (Africa Development, 2009)
Contents Performance and Power: Cultural Strategies for Contesting Hierarchy and Political Authority in Maazou Dan Alalo's Song 'Baudot' Antoinette Tidjani Alou ...................... 1 Linguistic Diversity, Pluralism and National Development in Africa Beban Sammy Chumbow ....................... 21 Songs of the King's Wives: Women, Power and Performance in the Yoruba Public Sphere Bode Omojola ........................... 47 Contesting the African Public Sphere: A Philosophical Re-imaging of Power and Resistance in Ngugi's Wizard of the Crow M.S.C. Okolo .......................... 59 The Sphere In-between: Najib Mahfuz on Power, Status and Authority in Africa's Public Sphere Oladosu Afis Ayinde .................... 81 Also in this Issue Nigeria's Niger Delta: Understanding the Complex Drivers of Violent Oil-related Conflict Cyril Obi ...........................103 Des lançados aux expatriés : « l'Ethnie Blanche » entre les fleuves Sénégal et Casamance Armonia Pérez Crosas ..................... 129 Les dessous de l'opération Licorne en Côte d'Ivoire : pour une lecture géopolitique nouvelle des interventions françaises en Afrique Mathieu Adjagbe ..................... 159 La guerre dans les médias, les médias dans la guerre en Côte d'Ivoire Raoul Germain Blé ...................... 177